Concentrated Growth Factors Promote hBMSCs Osteogenic Differentiation in a Co-Culture System With HUVECs - Liao, Yunyang; Fang, Youran; Zhu, Hanghang; Huang, Yue; Zou, Gengsen; Dai, Bowen; Rausch, Macro Aoqi; Shi, Bin (Frontiers in Bioengineering and Biotechnology, 2022)
Osteogenesis is a complex physiologic process that occurs during bone regeneration. This process requires several growth factors that act on bone marrow-derived mesenchymal stem cells (BMSCs). Concentrated growth factor (CGF) is a new-generation platelet-rich derivative that is an appealing autologous material for application in tissue repair and bone regenerative medicine because it contains a variety of fibrin and growth factors. In this study, the effects of CGF on the proliferation and osteogenic differentiation of hBMSCs and human umbilical vein endothelial cells (HUVECs) were explored with in vitro cell co-culture experiments. HBMSCs and HUVECs were directly co-cultured at the ratio of 1:2 under different concentrations (0%, 2%, 5%, 10%, 20%) of CGF for 7 days. Alkaline phosphatase (ALP) staining and quantitative reverse transcription polymerase chain reaction were used to detect the effects of CGF on the expression of osteogenic genes (ALP, osteocalcin [OCN], type I collagen [COL-1], Runt-related transcription factor 2 [RUNX2]) and connexin 43 (CX43). RNA sequencing was used to explore potential regulated genes and signaling pathways that affect the osteogenesis of co-cultured hBMSCs exposed to CGF. The results showed higher expressions of ALP, COL-1, RUNX2, OCN, and CX43 in the direct co-culture group containing 10% CGF compared to the direct co-culture group without CGF and the indirect co-culture group. In summary, 10% CGF can significantly promote osteogenesis in hBMSCs directly co-cultured with HUVECs. Intercellular communication between the direct co-culture of hBMSCs and HUVECs through CX43 may be one of the main regulatory mechanisms.